Thwarted belongingness and empathy's relation with organizational culture change - de Grandpré, Éloïse; Suurd Ralph, Cindy; Hiller, Emily (Frontiers in Psychology, 2024)
In response to several high-profile cases of senior leaders in the Canadian Armed Forces (CAF) being accused of various forms of sexual and professional misconduct, the organisation has committed to culture change. Drawing on the group engagement model and empirical evidence, we propose that CAF members' experience of thwarted belongingness reduces their capacity to show empathy, which in turn affects their support for culture change. Based on data from 139 Naval and Officer Cadets at the Royal Military College of Canada, thwarted belongingness was indirectly and negatively associated with support for culture change, through its impact on empathy. Efforts to change the culture of the CAF may need to consider improving members' levels of belongingness and, by extension, their levels of empathy. Implications for inclusion efforts are discussed.